2016
DOI: 10.3892/ijmm.2016.2630
|View full text |Cite
|
Sign up to set email alerts
|

p-CREB-1 promotes hepatic fibrosis through the transactivation of transforming growth factor-β1 expression in rats

Abstract: Abstract. Phosphorylated cAMP-responsive element binding protein-1 (p-CREB-1) is an important transcription factor which has been reported to be implicated in fibrogenesis. However, the association between p-CREB-1 and transforming growth factor-β1 (TGF-β1)-mediated liver fibrogenesis remains poorly understood. In the present study, exogenous TGF-β1 recombinant protein was used to activate hepatic stellate cells (HSCs), and we established a rat model of tetrachloromethane (CCl 4 )-induced liver fibrosis. Loss-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…46 In contrast, another report showed that CREB promoted hepatic fibrosis through the transactivation of TGFβ expression in rats. 47 Thus, there is a possibility that CREB is a key factor involved in the activity of CnP. We confirmed that TGFβ expression of CAF was decreased by CnP treatment ( Figure S6).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…46 In contrast, another report showed that CREB promoted hepatic fibrosis through the transactivation of TGFβ expression in rats. 47 Thus, there is a possibility that CREB is a key factor involved in the activity of CnP. We confirmed that TGFβ expression of CAF was decreased by CnP treatment ( Figure S6).…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, CREB has previously been shown to regulate inflammatory responses by directly regulating gene transcription of proinflammatory genes, such as IL‐6 and TNF‐α, and CREB silencing has been shown to reduce the levels of IL‐6, IL‐8, and CCL2 in malignant mesothelioma cells . In contrast, another report showed that CREB promoted hepatic fibrosis through the transactivation of TGF‐β expression in rats . Thus, there is a possibility that CREB is a key factor involved in the activity of CnP.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that autophagy promotes invasion of hepatocarcinoma cells by inducing TGF‐β1‐dependent EMT . Here, we provided further evidence showing that autophagy‐induced TGF‐β1 expression in hepatocarcinoma cells by activating cAMP/PKA/CREB signalling, consistent with previous reports demonstrating that p‐CREB can induce TGF‐β gene expression both in normal cells and in cancer cells by directly binding to the CRE site in the TGF‐β gene promoter . This autophagy‐induced activation of cAMP/PKA/CREB signalling was dependent on degradation of PDE4A based on the fact that inhibition of autophagy preserved PDE4A expression but inactivated cAMP/PKA/CREB signalling; however, inhibition of PDE4A‐activated cAMP/PKA/CREB signalling in autophagy‐deficient hepatocarcinoma cells, indicating a negative regulatory mechanism of cAMP/PKA/CREB signalling triggered by autophagy in hepatocarcinoma cells under starvation.…”
Section: Discussionsupporting
confidence: 90%
“…p‐CREB was reported to induce TGF‐β1 expression by binding to the CRE site in the TGF‐β1 gene promoter . Since activation of cAMP/PKA/CREB signalling was significantly promoted by autophagy (Figure ), and autophagy also induced TGF‐β1 expression in hepatocarcinoma cells under starvation, we further investigated the role of cAMP/PKA/CREB signalling in autophagy‐induced TGF‐β1 expression in HepG2 and BEL7402 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation